Decolonising Durkheimian Conceptions of the International: Colonialism and Internationalism in the Durkheimian School during and after the Colonial Era. Issue 1 (1st December 2021) - Mallard, Grégoire; Terrier, Jean
Abstract : Over the past 20 years, numerous scholars have called upon social scientists to consider the colonial contexts within which sociology, anthropology and ethnology were institutionalised in Europe and beyond. We explain how historical sociologists and historians of international law, sociology and anthropology can develop a global intellectual history of what we call the 'sciences of the international' by paying attention to the political ideas of the Durkheimian school of sociology. We situate the political ideas of the central figures explored in this special issue—Émile Durkheim, Marcel Mauss, Bronisław Malinowski and Alfred Métraux—in their broader context, analysing their convergence and differences. We also reinterpret the calls made by historians of ideas to 'provincialise Europe' or move to a 'global history', by studying how epistemologies and political imaginaries continued by sociologists and ethnologists after the colonial era related to imperialist ways of thinking.